Brokedown Palace - Jonathan Kaplan; Pullman, Bill, 1953-; Daniel Lapaine; Jacqueline Kim; Kate Beckinsale; Lou Diamond Phillips; Claire Danes (USA Adam Fields Productions, 1999)
Alice and Darlene, best friends, decide to take a trip to Thailand to celebrate high-school graduation. While there, they are befriended by charming Australian rogue Nick Parks. Nick convinces them to take a weekend side trip to Hong Kong, but at the airport, they are busted for smuggling drugs. They are convicted in a show trial and sentenced to 33 years in desperation, they contact Yankee Hank, an American lawyer based in Thailand who has been reported to be helpful if you've got the cash.
Two women are arrested for smuggling while vacationing in Thailand.
Language: English
Subtitles: English, Norwegian, Swedish, Turkish
Keywords: Drama